White vs. colored coats: Which reduces dental anxiety better? - Elif Kilic; Sema Aydinoglu; Dilara Nil Gunacar (BMC Oral Health)
Abstract Backgrounds To evaluate the effect of colored vs. white coat wear on dental anxiety in children using psychometric, projective, and physiological methods. Methods The participants were divided into two groups by the pediatric dentist based on the participants’ coat color (white vs. colored), and procedures were performed during two separate appointments for both groups: dental examination (DE) and preventive dental treatments (PDT). The blood pressure, pulse rate, and saturation were recorded before and after each appointment. Anxiety was assessed using the Modified Child Dental Anxiety Scale Faces Version (MCDASf) before and after the appointments and the Child Drawing: Hospital (CD: H). Chi-Square, Mann-Whitney U test, Wilcoxon Signed-Rank test, and t-test were used for analysis. The statistical significance level was evaluated as P < 0.05. Results Compared to the colored coat group, MCDASf values ​​recorded before both appointments were higher in the white coat group (P = 0.019; P = 0.034). Also, it was observed that the CD: H values of the colored coat group were significantly lower after PDT (P = 0.037). According to the coat groups, there was a significant difference between pulse rates measured before and after both appointments (P = 0.026; P = 0.017; P = 0.008; P = 0.004). Conclusions The clinician’s coat color selection impacts children’s dental anxiety. The findings suggest that colored coats are more effective than white coats in relieving dental anxiety.